The Difference of Antibacterial Power Between Cocoa Peel (Theobroma cacao) Extract 6% Compared to NaOCL 5% Againts Lactobacillus acidophilus - Tamara Yuanita; Dian Agustin Wahjuningrum; Mega Selvia (Conservative Dentistry Journal, 2021)
Background: Lactobacillus acidophilus is a gram-positive rod-shaped bacteria which mostly causes chronic caries lesions. In the process of cavity preparation it is reported that it is not possible to remove all microorganisms and even bacteria can survive even after removal of the necrotic tissue. Efforts to stop the growth of these bacteria are by chemical cavity cleanser using a 5% NaOCl, but this material have disadvantages including irritating periradicular tissue, unpleasant odor, and toxicity. Due to its disadvantages, it is hoped that natural ingredients can be used as alternatives. Cocoa peel extract has active compounds of tannins, flavonoids, alkaloids, terpenoids, and saponins which have antibacterial ability with a concentration of 6% according to the non-toxic minimum kill concentration of Lactobacillus acidophilus. Purpose: To analyze the difference in antibacterial power between the extract of cocoa bark with a concentration of 6% compared to 5% NaOCl against Lactobacillus acidophilus. Methods: This study was a laboratory experimental in vitro with a post test-only control group design. Using diffusion method against Lactobacillus acidophilus grown in tubes containing BHIB, then cultured in a petridish which contains a nutrient agar and is divided into 2 parts extract cocoa peel extract 6% and NaOCl 5%, then each petridish given a paper disc that has been poured 10μl by each material, then incubated inthe incubator for 2x24 hours at 37oC and observe the diameter of the inhibition zone formed using a caliper. Results: The average diameter of the inhibition zone formed in the 6% cocoa peel extract was 11.8375 mm and NaOCl 5% was 26.0344 mm against Lactobacillus acidophilus. Conclusion: There is a difference in antibacterial power between 6% cocoa peel extract and 5% NaOCl against Lactobacillus acidophilus.